Incidencia de la inversión extranjera directa y la industria manufacturera en el crecimiento económico de Ecuador, en el período 1980 - 2018: Técnicas de cointegración” - Pintado Cuenca, Karen Mishell (2020)
Foreign Direct Investment and the manufacturing industry are two important components to contribute to growth and economic evolution in developing countries, in which Ecuador is located, that is why our research has focused on studying the incidence of Foreign Direct Investment and the manufacturing industry in the economic growth of Ecuador, in the period from 1980 to 2018, which had as main objective to analyze the incidence of foreign direct investment and the manufacturing industry in the economic growth of Ecuador during the period 1980 - 2018, using cointegration techniques to verify compliance. The results indicate that foreign direct investment has a positive relationship with economic growth in the short term, but this relationship is not evident in the long term, while with the manufacturing industry there is a positive relationship with economic growth in the short and long term. long term. Also, a bidirectional Granger causality is evidenced between economic growth and the manufacturing industry, such causality did not exist with foreign direct investment. Finally, the investigative document suggests generating state policies aimed at generating confidence in investors, to obtain greater foreign flows to the country, and thus contribute to the adoption of technology in Ecuador and with this help the manufacturing industry in its production, generating greater exports for the country, contributing to a more sustainable economic growth.